A Systematic Review of Physical Activity Programs for Older People Receiving Home Care Services - Burton, Elissa; Lewin, Gill; Boldy, Duncan (Human Kinetics Inc, 2015)
The proportion of older people living in our communities is rising and to live independently some require assistance from home care services. Physical activity can improve and maintain function, strength and balance, which is important for those receiving home care. This study reviewed the evidence on physical activity/exercise interventions trialled with older people receiving a home care service. A systematic review of studies published from January 1982 to September 2012, from five databases, was undertaken. Inclusion criteria were: aged 65+ years; community dwelling; no dementia diagnosis; receiving home care services; and a physical activity/exercise program. Eight articles were included and results show there were few consistencies between intervention types, groups, outcome measures and follow-up. Study quality was mixed. Future studies should include pragmatic randomized controlled trials involving home care practitioners and their clients to gain “real world” knowledge of what interventions are effective and can be delivered within this setting.